2014
DOI: 10.1556/avet.2013.046
|View full text |Cite
|
Sign up to set email alerts
|

Effects of skim-milk supplementation on the quality and penetrating ability of boar semen after long-term preservation at 15 °C

Abstract: This study investigated the effects of skim-milk supplementation on the quality and penetrating ability of boar semen preserved at 15 °C. When boar semen samples were preserved in Modified Modena extender supplemented with various concentrations (0, 7.5, 15, 30 and 50 mg/mL) of skim milk powder at 15 °C for 4 weeks, higher sperm motility and viability were observed in the case of 7.5 mg/mL skim-milk supplementation compared with the control group (0 mg/mL) during the preservation (P < 0.05). When in vitro matu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Semen collection and cryopreservation were performed according to the method described by Namula et al () and Karja et al () with minor modifications, respectively. In brief, semen samples were collected once from five fertile Large White boars (2–3 years old) by the gloved‐hand technique in November 2017.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Semen collection and cryopreservation were performed according to the method described by Namula et al () and Karja et al () with minor modifications, respectively. In brief, semen samples were collected once from five fertile Large White boars (2–3 years old) by the gloved‐hand technique in November 2017.…”
Section: Methodsmentioning
confidence: 99%
“…Semen collection and cryopreservation were performed according to the method described by Namula et al (2014)…”
Section: Semen Collection and Cryopreservationmentioning
confidence: 99%
“…In addition, because of the limited ability of sperm to establish a powerful defense system of antioxidants, a great deal of effort has been invested to search for exogenous antioxidants to prevent oxidative damage (Zhang et al, 2017). In general, enzymatic antioxidants (such as superoxide dismutase, catalase, and glutathione peroxidase) and non-enzymatic antioxidants (such as ascorbic acid, α-tocopherol, taurine, and cysteine) provide effective defense mechanisms for sperm (Namula et al, 2014). Indeed, previous studies have indicated that adding antioxidant agents to bull (Tvrda et al, 2016), ram (Zhao et al, 2017), goat (Shafiei, Forouzanfar, Hosseini, & Esfahani, 2015), boar (Gadani, Bucci, Spinaci, Tamanini, & Galeati, 2017), canine (Setyawan et al, 2016), and human (Azadi, Tavalaee, Deemeh, Arbabian, & Nasr-Esfahani, 2017) semen can protect sperm from ROS attack and improve sperm quality parameters (Bansal & Bilaspuri, 2010).…”
mentioning
confidence: 99%
“…During the process of freezing and thawing, the occurrence of lipid peroxidation caused by the accumulation of ROS and the removal of natural antioxidants in the seminal plasma could severely damage the lipid tails in the sperm plasma membrane, leading to undesirable effects on spermatozoa functions and their penetrability (Bansal and Bilaspuri, 2010). In a previous study, we reported that the supplementation of skim milk powder to the semen extender improves the motility and viability of boar sperm after long-term liquid preservation (Namula et al, 2014). Skim milk has been considered to be a non-enzymatic antioxidant that functions by the sulphhydryl groups (Bustamante Filho et al, 2009).…”
Section: Discussionmentioning
confidence: 99%